The Importance of Lean Knowledge Management For A Successful Lean Management Implementation In The Malaysian Public Sector - Zarifa, Zulkeflee; Gusman, Nawanir; Airin, AbdulGhani; Norhana, Aripin (Penerbit Universiti Malaysia Pahang, 2022)
The Malaysian public sector has implemented many programs to enhance service performance. One of them is lean management. Since the 2000s, lean management has been popular among the public sector to improve service quality and reduce operating costs. However, adequate lean knowledge to strengthen lean implementation is essential. Therefore, the purpose of this study is to address the role of lean knowledge management for effective lean management implementation in the Malaysian public sector. This cross-sectional quantitative survey has collected 131 responses from public organisations in Malaysia selected through a stratified random sampling technique. The data were analysed using the structural equation modelling (SEM) approach with SmartPLS 4.0. Findings show that lean knowledge management significantly affects lean management implementation. Theoretically, this study will aid academics and practitioners in choosing the best road forward in achieving a successful lean management implementation that will lead to a competitive advantage. From a practical standpoint, the findings of this study provide several recommendations to practitioners. They can comprehend and assess the potential benefits of implementing lean management on Malaysia's public sector performance.